Akurasi Metode IDW dan Kriging untuk Interpolasi Sebaran Sedimen Tersuspensi - Gatot H. Pramono (Universitas Muhammadiyah Surakarta, 2008)
Physical conditions of seawater in coastal area can be studied by sampling at several locations. To perform spatial analysis, the data should be interpolated to get the values between sample points. Several approaches for interpolation may result in different outcomes. The purpose of this research is to compare Inverse Distance Weighted (IDW) and Kriging methods. Their parameters are studied using the total suspended sediments in Maros area, South Sulawesi. The results show that the more accurate interpolation is obtained by using IDW method than using Kriging method.